The Relationship Between APTT Values and LDL Levels in Heart Disease Patients with a History of Hypercholesterolemia - Anak Agung Istri Ulandari; I Gst Pt Agus Ferry Sutrisna Putra; Lia Cahya Sari (Jurnal Kesehatan Cendikia Jenius, 2026)
Introduction: Heart disease with a history of hypercholesterolemia is associated with the atherosclerotic process, which may affect coagulation mechanisms, making the assessment of LDL and APTT important to analyze. Objective: This study aimed to determine the relationship between Activated Partial Thromboplastin Time (APTT) and Low-Density Lipoprotein (LDL) levels in heart disease patients with a history of hypercholesterolemia. Methods: The study employed an analytical observational cross-sectional design with 40 samples selected through consecutive sampling, conducted at the Laboratory Installation of RSUD Bangli from November 1 to December 31, 2025. Data were obtained from 8–12-hour fasting blood samples; LDL levels were analyzed using the BA 200 analyzer, while APTT was measured using the STart Max Stago instrument. Data were analyzed using Spearman’s Rank correlation test. Results: The results showed that 50% of respondents had normal APTT values and 50% had prolonged APTT, while LDL levels were predominantly in the normal category (75%), followed by the high category (25%). Spearman’s test yielded p=0.759 and r=−0.050. Conclusion: There was no significant relationship between LDL and APTT, indicating that LDL levels are not directly associated with changes in APTT. Further studies are recommended to evaluate other factors that may influence coagulation.